Csr And Ethnicity: A Case Study Of Malay Marginalisation In Unesco George Town World Heritage Site, Penang, Malaysia - Suhaimi, Dina Miza (2020)
This thesis offers an analysis of Malay marginalisation in UNESCO George Town World Heritage Site, Penang, Malaysia (the Site). The present analysis towards the battles to conserve and promote the Site’s long-standing heritage have generally revolved around federal and state-level organisations; neglecting the voices of marginalised group. The community of concern here is the Malays. The objectives of this thesis are four-fold: (i) to investigate the patterns of ethnic marginalisation perceived by the Malay community in the Site, and to analyse, if at all, the meanings of ethnic marginalisation they are attached to; (ii) to construct the emergent typologies stemming from the meanings of ethnic marginalisation conveyed by Malay community; (iii) to examine the patterns of ethnic marginalisation occurring in ethnic composition of the organisations; as well as CSR projects in the Site; and (iv) to construct the emergent typologies stemming from the patterns of ethnic marginalisation in ethnic composition of the organisations; as well as CSR projects in the Site.